Mapa turístico de la parroquia Belisario Quevedo, del cantón Latacunga, provincia de Cotopaxi. - Córdova Constante, Nicole Vivian (2024)
The present research focuses on the Belisario Quevedo Parish, located in the Latacunga Canton, Cotopaxi Province. Belisario Quevedo stands out for its productivity and livestock development, as well as extensive green areas and natural landscapes that encourage various recreational activities such as hiking, cycling, boat trips, extreme sports, among others (GAD Belisario Quevedo, 2019). This research arises due to the lack of tourist information about the parish; therefore, the goal was to design an interactive tourist map that includes detailed information about complementary services, tourist and cultural attractions, resources, and available tourist infrastructure in the area, aimed at both local and foreign visitors. As a first step, bibliographic information was contrasted, obtaining information about the tourist attractions, resources, and tourist infrastructure of the parish. The available inventories used include the provincial GAD of Cotopaxi (2), the parish GAD of Belisario Quevedo (12), and MINTUR (1). Interviews with members of the parish GAD and owners of complementary services, on-site visits, and field trips were also conducted to gather more detailed information about the area. The parish has 12 tourist attractions, which are divided into natural attractions (5) and cultural attractions (7). Regarding tourist infrastructure, the parish has 30, which are divided into food and beverage services (20), activities (3), and lodging services (7). For the design of the interactive tourist map, key considerations were given to the main parish attractions, signage, real complementary services in the area, and other relevant elements. All the information obtained is based on on-site visits and interviews. The criteria for the design of the tourist map were established in accordance with the guidelines of the Ecuadorian Ministry of Tourism (MINTUR), including prioritization, surveys, accessibility, categorization, and inventory sheets. The interactive map of the Belisario Quevedo Parish features 12 tourist attractions and 30 pieces of tourist infrastructure. This map represents an initial milestone in highlighting the tourist potential of the parish, laying the groundwork for the creation of new tourism products and projects that encourage residents to undertake and safeguard their heritage, contributing significantly to the improvement of local economic activity.